THE INFLUENCE OF WORK ENVIRONMENT AND ORGANIZATIONAL CULTURE ON TEACHER JOB SATISFACTION IN SUPPORTING ECONOMIC DEVELOPMENT IN THE EDUCATION SECTOR - Muspawi, Mohamad; Sofwan, Muhammad; yantoro, Yantoro; Mulyadi, Mulyadi; Septiana, Rosa Rina (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
This study aims to explain the influence of the work environment on the job satisfaction of honorary teachers at Senior High School Tanjung Jabung Barat. This research method is included in survey research with a quantitative approach. The data collection technique used is a questionnaire. The research data sources are primary data, namely questionnaires, and secondary data, namely Basic Education Data and related articles. The study’s results revealed a significant and simultaneous influence between the work environment and organizational culture on the job satisfaction of honorary teachers at Senior High School Tanjung Jabung Barat. So that work environment and organizational culture factors are given more attention to improving the job satisfaction of honorary teachers at Senior High School Tanjung Jabung Barat. The novelty of this study lies in the in-depth analysis of the role of the work environment and organizational culture in improving the job satisfaction of honorary teachers, with the implication that strategies to strengthen both factors can significantly improve their welfare and performance at Senior High School Tanjung Jabung Barat.